Spatial memory dissociations in mice lacking GluR1. - Reisel, D; Bannerman, D; Schmitt, W; Deacon, R; Flint, J; Borchardt, T; Seeburg, P; Rawlins, J (2002)
Gene-targeted mice lacking the AMPA receptor subunit GluR1 (GluR-A) have deficits in hippocampal CA3-CA1 long-term potentiation. We now report that they showed normal spatial reference learning and memory, both on the hidden platform watermaze task and on an appetitively motivated Y-maze task. In contrast, they showed a specific spatial working memory impairment during tests of non-matching to place on both the Y-maze and an elevated T-maze. In addition, successful watermaze and Y-maze reference memory performance depended on hippocampal function in both wild-type and mutant mice; bilateral hippocampal lesions profoundly impaired performance on both tasks, to a similar extent in both groups. These results suggest that different forms of hippocampus-dependent spatial memory involve different aspects of neural processing within the hippocampus.